Réponses

Meilleure réponse !
2014-10-01T20:18:01+02:00
A = 7,1 + 2,9 - 1 + 2
= 10,0 - 1 + 2
= 9,0 + 2
= 11

B = 31 - 10 x 2
= 31 - 20
= 11

C = 74 - 7 x (25 - (7 - 2) x 3)
= 74 - 7 x (25 - 5 x 3)
=  74 - 7 x (25 - 15)
= 74 - 7 x 10
= 74 - 70
= 4

  • 7MK
  • Explorateur
2014-10-01T20:21:22+02:00
A= 7,1+2,9-1+2
A= 7,1+2,9-0,5
A= (7,1+2,9) - 0,5
A= 10 + 0,5
A= 10,5

B=
31-10x2
B= 31-20
B= 11

C=
74-7x(25-(7-2) x 3)
C= 74-7×(25-5) × 3
C= 74-7×20×3
C= 74-420
C= -346
J'ai faussé j'ai mal vu c'est Pan59 qui a raison ^^
Pas grave merci quand même ^^